2023
DOI: 10.1186/s40634-023-00679-9
|View full text |Cite
|
Sign up to set email alerts
|

The quest for optimal femoral torsion angle measurements: a comparative advanced 3D study defining the femoral neck axis

Bert Van fraeyenhove,
Jeroen C. F. Verhaegen,
Jonas Grammens
et al.

Abstract: Purpose There is high variability in femoral torsion, measured on two-dimensional (2D) computed tomography (CT) scans. The aim of this study was to find a reliable three-dimensional (3D) femoral torsion measurement method, assess the influence of CAM deformity on femoral torsion measurement, and to promote awareness for the used measurement method. Methods 3D models of 102 dry femur specimens were divided into a CAM and non-CAM group. Femoral torsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…In the literature, the assessment of femoral torsion using 3D femur models often relies on landmark registration. In such approaches, proximal and distal femoral 3D models are realigned to the mechanical axis, and femoral torsion is evaluated as the intersection between the femoral neck axis and the retrocondylar plane [ 4 , 5 , 8 , 11 ]. However, it has been demonstrated that 3D measurements can be sensitive to how the femoral neck axis is defined [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the literature, the assessment of femoral torsion using 3D femur models often relies on landmark registration. In such approaches, proximal and distal femoral 3D models are realigned to the mechanical axis, and femoral torsion is evaluated as the intersection between the femoral neck axis and the retrocondylar plane [ 4 , 5 , 8 , 11 ]. However, it has been demonstrated that 3D measurements can be sensitive to how the femoral neck axis is defined [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…In such approaches, proximal and distal femoral 3D models are realigned to the mechanical axis, and femoral torsion is evaluated as the intersection between the femoral neck axis and the retrocondylar plane [ 4 , 5 , 8 , 11 ]. However, it has been demonstrated that 3D measurements can be sensitive to how the femoral neck axis is defined [ 8 ]. In this recent study, van Fraeyenhove et al conducted a study examining femoral torsion through five different 3D analyses based on the selection of the femoral neck axis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations